2019
DOI: 10.1021/jacs.9b04649
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Interference Engineering of Nanoporous Graphene for Carbon Nanocircuitry

Abstract: Bottom-up prepared carbon nanostructures appear as promising platforms for future carbon-based nanoelectronics, due to their atomically precise and versatile structure. An important breakthrough is the recent preparation of nanoporous graphene (NPG) as an ordered covalent array of graphene nanoribbons (GNRs). Within NPG, the GNRs may be thought of as 1D electronic nanochannels through which electrons preferentially move, highlighting NPG's potential for carbon nanocircuitry. However, the π-conjugated bonds bri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 35 publications
5
46
0
Order By: Relevance
“…To present the structures more clearly, the meta-CNT and para-CNT are unfolded along the Z axis to form nanoribbon structures, as shown in Figure 1c,d. The QI-based graphene nanoribbon structures have already been synthesized by Calogero et al, [55] indicating that the QI-based NCNT is expected to be synthesized in experiments. The calculated electron transmission properties of perfect-CNT, meta-CNT, and para-CNT devices are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…To present the structures more clearly, the meta-CNT and para-CNT are unfolded along the Z axis to form nanoribbon structures, as shown in Figure 1c,d. The QI-based graphene nanoribbon structures have already been synthesized by Calogero et al, [55] indicating that the QI-based NCNT is expected to be synthesized in experiments. The calculated electron transmission properties of perfect-CNT, meta-CNT, and para-CNT devices are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…For the NPGs, all fall within the trend of the GNRs. We note that the meta-and para-NPGs show little difference in the anisotropy they induce in graphene, despite their significantly different transport properties in isolation 36 . Finally, the NPG-8 and NPG-10 structures fall on the other side of the optimal width/band gap.…”
mentioning
confidence: 79%
“…Specifically, we consider two other configurations of NPG that were studied in Ref. 36. These structures are the same as that in Fig.…”
mentioning
confidence: 99%
“…For this reason, researchers have been finding a wide variety of applications such as in nanoelectronics [4,5], energy storage [6,7], water purification [8] and as coated composite materials [9]. In addition to these applications, the nanoporous graphene (NPG) membranes promise great utility in seawater desalination [10,11], carbon dioxide separation [12][13][14] and the nanoribbons of NPG may be thought of as unidimensional channels for electronic applications (nanocircuity), i.e., for directing electrons through predesigned paths via nanoporous [15]. In this scenario, previous studies have reported that permeability of the NPG membrane is approximately three orders of magnitude greater than the latest generation (commercial) reverse osmosis, where salt ions are rejected at 100 % [10].…”
Section: Introductionmentioning
confidence: 99%